Effects of electroconvulsive therapy on nitrosative stress and oxidative DNA damage parameters in patients with a depressive episode. (1st September 2022) - Karayağmurlu, Elif; Elboğa, Gülçin; Şahin, Şengül Kocamer; Karayağmurlu, Ali; Taysı, Seyithan; Ulusal, Hasan; Altındağ, Abdurrahman
Abstract: Background: Few studies have investigated the relationship between electroconvulsive therapy (ECT) and markers of nitrosative stress and oxidative DNA damage. Objective: The aim of this study is to examine changes in nitrosative stress and oxidative DNA damage in patients with a depressive episode treated with ECT. Methods: The current study included 48 patients with a depressive episode treated with ECT and 30 healthy control participants. First, the serum nitrosative stress markers of nitric oxide (NO), nitric oxide synthase (NOS), and peroxynitrite (ONOO-) and the oxidative DNA damage marker 8-hydroxy-2′-deoxyguanosine (8-OHdG) were compared between the study and control groups. These parameters were also compared pre- and post-treatment for the study group. Results: NO, NOS, and ONOO- levels were significantly higher in patients with depressive disorder (DD) than in the control group. NO and NOS levels significantly decreased in the ECT group after treatment while 8-OHdG levels significantly increased. Conclusions: The study findings suggest that ECT may have reduced nitrosative stress levels while increasing oxidative DNA damage. More research is now needed to better understand the issue. KEY POINTS: Nitrosative stress levels can increase in patients with depressive disorder. Electroconvulsive therapy may reduce nitrosative stress while increasıng oxidative DNA damage. These results suggest that nitrosative stress plays an important role in the mechanism of action of electroconvulsive therapy.